2019
DOI: 10.1093/abm/kay096
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness-Oriented Recovery Enhancement Versus Social Support on Negative Affective Interference During Inhibitory Control Among Opioid-Treated Chronic Pain Patients: A Pilot Mechanistic Study

Abstract: Background Among opioid-treated chronic pain patients, deficient response inhibition in the context of emotional distress may contribute to maladaptive pain coping and prescription opioid misuse. Interventions that aim to bolster cognitive control and reduce emotional reactivity (e.g., mindfulness) may remediate response inhibition deficits, with consequent clinical benefits. Purpose To test the hypothesis that a mindfulness-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 70 publications
2
16
0
Order By: Relevance
“…In prescription opioid users with chronic pain conditions, treatment with MORE led to decreased errors of commission in an emotional Go/NoGo task when faced with pain-related distractors. Emotional response inhibition was furthermore correlated with the length of mindfulness practice as well as nonreactivity and reduced pain severity at follow-up [76].…”
Section: Top-down Controlmentioning
confidence: 97%
“…In prescription opioid users with chronic pain conditions, treatment with MORE led to decreased errors of commission in an emotional Go/NoGo task when faced with pain-related distractors. Emotional response inhibition was furthermore correlated with the length of mindfulness practice as well as nonreactivity and reduced pain severity at follow-up [76].…”
Section: Top-down Controlmentioning
confidence: 97%
“…These changes may help overcome prepotent motor responses, reduce the cognitive effort required for decision making about appetitive health behaviors, and diminish susceptibility to automatic behaviors in response to negative affect. 106 , 132 …”
Section: Mindful Self-regulationmentioning
confidence: 99%
“…Regarding studies on mindfulness effects on pain scale of other patients, it is possible to refer to the study done by Ahmadi et al, which showed that in cancer patients mind-consciousness variance can result in increase of their life quality (56). In a systematic and meta-analysis review study done by Garland et al, it was shown that mindfulness-based stress reduction interventions (MBSR) reduce chronic pain of the patients (57). Furthermore, in the systematic and meta-analysis review study done by Ngamkham et al on the cancer patient group, the findings showed that mindfulness intervention results in pain reduction in this group of patients (58), which is consistent with the results of the present study indicating a meaningful statistical correlation between mindfulness and pain severity.…”
Section: Discussionmentioning
confidence: 99%